Nigeria : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
This 2014 Article IV Consultation highlights that inflation in Nigeria has remained in single digits for two years, and the banking sector, which has a strong capital base, is expanding credit. The trade surplus has been declining since the second quarter of 2013 on lower oil exports and continued strong growth of imports, and gross international reserves have been falling. The general government fiscal deficit and public debt have been kept low. The Executive Directors have commended authorities for progress in promoting Nigeria's economic diversification and for their macroeconomic response to collapsing export prices.